MocKINgbIRd - Erskine, Kathryn (London, United Kingdom : Usborne Publishing Ltd., 2018)
Caitlin misses her brother every day. Since his death in a school shooting, she has no one to explain the world to her. And for Caitlin, the world is a confusing place. She hates it when colours get mixed up, prefers everything to be black-and-white, and needs to check her Facial Expressions Chart to understand emotions. So when Caitlin reads the definition of "closure", she decides that's what she needs. And as she struggles to find it, a world of colour begins to enter her black-and-white life...
Keywords: English fiction; Families -- Virginia -- Fiction; Asperger's syndrome -- Fiction; Loss (Psychology) -- Fiction